2005
DOI: 10.1080/08035250410025104
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent abdominal pain: A five-year follow-up study

Abstract: To explore the long-term prognosis for children referred for recurrent abdominal pain (RAP), 44 children investigated for RAP 5 y ago were compared to a group of controls (n=88). The former RAP patients reported RAP, headache and school absence more frequently than controls. A high proportion of children referred with RAP have persistent symptoms, with more headache and school absence than controls. The diagnostic subgroup did not predict persistence of abdominal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 11 publications
0
45
0
1
Order By: Relevance
“…Longitudinal follow-up studies found that for a significant portion (25%–45%), pain symptoms persist 5 years later (18,19). Furthermore, some develop additional pain conditions such as headaches (19) or other somatic complaints (18).…”
Section: Outcomes Of Fapmentioning
confidence: 99%
“…Longitudinal follow-up studies found that for a significant portion (25%–45%), pain symptoms persist 5 years later (18,19). Furthermore, some develop additional pain conditions such as headaches (19) or other somatic complaints (18).…”
Section: Outcomes Of Fapmentioning
confidence: 99%
“…They scored significantly higher on hypochondriacal beliefs, showed a greater perceived susceptibility to functional disability by pain and other physical symptoms, and were more likely to report current treatment with psychoactive medication [23]. Conversely, in a study of Stordal et al [29], no differences in pain history, associated symptoms, atopy in the child or the family, laboratory findings and family history between those who continue to suffer from abdominal pain 5 years after initial evaluation and those who do not were found.…”
Section: Introductionmentioning
confidence: 99%
“…Children with chronic pain may experience significant impairment, including increased healthcare utilization (3, 4), academic difficulties and social problems (3). For a large number of youth with chronic pain, symptoms persist for five years or longer (5-7). Cognitive behavioral therapy (CBT) focused on pain coping skills training is known to improve outcomes for youth with chronic pain in research trials (8-10) and in clinical settings (11, 12).…”
mentioning
confidence: 99%